2012
DOI: 10.13031/2013.42508
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Four Field-Scale Agricultural Drainage Denitrification Bioreactors in Iowa

Abstract: Recently, interest in denitrification bioreactors to reduce the amount of nitrate in agricultural drainage has led to increased installations across the U.S. Midwest. Despite this recent attention, there are few peer-reviewed, field-scale comparative performance studies investigating the effectiveness of these denitrification bioreactors. The object of this work was to analyze nitrate removal performance from four existing bioreactors in Iowa, paying particular attention to potential performance-affecting fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
128
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(148 citation statements)
references
References 34 publications
16
128
4
Order By: Relevance
“…The nitrate removal percentage was similar to many reports in the literature, such as Christianson et al (2012b), who reported a range of 12 to 76% for four bioreactors in Iowa, and Verma et al (2010), who reported a range of 42 to 98% for three bioreactors in central Illinois. The percentage effectiveness and mass of nitrate removed decreased greatly in Year 2 (2013), with only 72 kg N removed from a large tile input of 2127 kg N. The mass and tile concentration of nitrate N in 2013 were high due to leftover nitrate on the field after the drought and failed seed corn in 2012.…”
Section: Bioreactor Performance and Controls On Nitrate Removalsupporting
confidence: 88%
See 1 more Smart Citation
“…The nitrate removal percentage was similar to many reports in the literature, such as Christianson et al (2012b), who reported a range of 12 to 76% for four bioreactors in Iowa, and Verma et al (2010), who reported a range of 42 to 98% for three bioreactors in central Illinois. The percentage effectiveness and mass of nitrate removed decreased greatly in Year 2 (2013), with only 72 kg N removed from a large tile input of 2127 kg N. The mass and tile concentration of nitrate N in 2013 were high due to leftover nitrate on the field after the drought and failed seed corn in 2012.…”
Section: Bioreactor Performance and Controls On Nitrate Removalsupporting
confidence: 88%
“…A wide range of nitrate removal effectiveness (up to 98% nitrate reductions) in laboratory and field studies has been reported in the literature (Greenan et al, 2009;Chun et al, 2009Chun et al, , 2010Moorman et al, 2010;Verma et al, 2010;Woli et al, 2010;Christianson et al, 2012b;Bell et al, 2015). Most have been designed as plasticlined trenches, filled with mixed-species wood chips, that receive tile flow from fields ranging from 1 to 20 ha in size (e.g., Woli et al, 2010;Christianson et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Among edge-of-field practices, woodchip bioreactors are recognized as one of the promising technologies to remove nitrate from tile drainage (IDALS, 2013). A comparative study of field bioreactors at four separate locations in Iowa reported an average nitrate removal of 43 percent for treated drainage water (Christianson et al, 2012), demonstrating that such systems could achieve reductions close to those targeted by the Hypoxia Task Force. However, the performance of bioreactors is highly variable, with lower removal efficiencies occurring when temperatures are low, or flow is high (i.e., when hydraulic retention time (HRT) are low) (Hoover et al, 2015;Robertson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found riparian buffers to be ineffective in locations where agricultural fields are drained via tiles directly into streams and ditches (Kovacic et al, 2000;Lemke et al, 2012). Thus, additional engineered solutions at the end of tiles are recommended, such as constructed wetlands and bioreactors (Kovacic et al, 2000;Woli et al, 2010;Christianson et al, 2012). Seasonality of fertilizer applications and runoff rarely correlate with the timing of poor water quality, creating a complex management situation (Royer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%